(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
On February 21st, 2020, the first case of severe acute respiratory failure due to the coronavirus 2 (SARS-CoV-2), was identified in Italy. As of March 8th, 2020, Italy was the 2nd most affected country in the world. As of March 6th, 2020, the Italian Society of Anesthesia and Intensive Care (SIAARTI) published the clinical ethics Recommendations for the allocation of intensive care treatments in exceptional, resource-limited circumstances, in order to support the clinicians involved in the care of critically-ill CoViD-19 patients and facing a scenario of imbalance between supply and demand of ICU beds. The SIAARTI Recommendations have raised stir within the medical-scientific community, and also among legal experts, philosophers, and in the media. The aims of this paper are: 1) to summarize the ethical foundations of the SIAARTI recommendations; 2) to report the scientific evidence on which the recommendations are grounded; 3) to describe the economic, organizational and epidemiological context; 4) to reply to some of the criticisms.